Developing chitosan-based composite nanofibers for supporting metal catalysts. (28th September 2015) - Shao, Linjun; Ren, Yuan; Wang, Zining; Qi, Chenze; Lin, Yao
Abstract: Using electrospinning technique to prepare chitosan (CS) nanofibers from an inexpensive solvent such as acetic acid has been a challenge, due to the lack of sufficient entanglements in these semi-rigid polyelectrolytes. Incorporating polymers such as poly(methacrylic acid) (PMAA) into the solution lowers the entanglement concentration of the polymers, and make all three morphology regimes (polymer droplets, beaded nanofibers and nanofibers with uniform thickness) accessible to electrospinning method. Uniform composite nanofibers are found at concentrations well above the entanglement concentration. The thickness and morphology of nanofibers can be regulated by addition of small amount of organic solvents such as dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). The composite nanofibers are subsequently crosslinked at an elevated temperature to improve their thermal and solvent stability. The mechanical properties of the crosslinked CS/PMAA fibers can be modulated by varying the amount and molecular weight of PMAA incorporated in the blend. The composite fiber materials provide a useful platform to support a variety of catalysts. As a demonstration, palladium catalyst has been immobilized on the crosslinked CS/PMAA nanofibers to carry out Mizoroki–Heck cross-coupling reactions of aromatic halides and acrylates. We found remarkable catalytic efficiency and stability in these materials. We also demonstrate that, by the "post-modification" of the nanofibers with ligands that chelate metal catalysts, a variety of metal catalysts can be incorporated into the fiber platform, with further improved stability and activity. Graphical abstract: Abstract : A general approach to obtain composite chitosan nanofibers is proposed. The method is based on mechanistic understanding of chain entanglements in solution. The composite fibers provide a useful platform to support a variety of catalysts. "Post-modification" of the fibers further improves the stability of supported catalysts.